Origin and temperature on the germination of beggartick seeds - Barros, Renato T. de [UNESP]; Martins, Cibele C. [UNESP]; Silva, Givanildo Z. da [UNESP]; Martins, Dagoberto [UNESP] (Univ Federal Campina Grande, 2017)
The invasive behavior of beggarticks (Bidens pilosa L.) in cropped areas is due to its ecological adaptation and aggressive regeneration, which is dependent on seed germination. The objective of this research was to verify the effects of B. pilosa seed origin and temperature on seed germination. The seeds were collected in Entre Rios do Oeste, PR, Botucatu, SP, Capao Bonito, SP, Sao Joaquim da Barra, SP, Sertaozinho, SP, Selviria, MS, Barra do Garcas, MT, Areia, PB and Manaus, AM. The seeds were evaluated regarding moisture content, 1000-seed weight, germination speed index and germination at 60 days (normal seedlings, dormant seeds and dead seeds) at the temperatures of 10, 15, 20, 25, 30, 35, 40, and 45 degrees C. The replicates were distributed according to a completely randomized design in a 9 x 8 factorial arrangement (seed origin x temperature) with four replicates. The means were compared by the Scott-Knott test. B. pilosa seeds germination depends on seed origin. Temperatures higher than 35 degrees C are lethal to the seeds. The temperature of 15 oC allows maximum germination in the shortest time whichever the seed origin.
Keywords: Bidens pilosa; weed; production sites; dormancy